Youth Supervision Based on Islam Provided by Muslim Leaders in Southern Thailand - Laeheem, Kasetchai; Madreh, Abdullohmalik (Kasetsart Journal of Social Sciences, 2014)
The purpose of this qualitative study was to investigate situations and problems of youth supervision based on Islam by Muslim leaders in three southern border provinces of Thailand. In-depth interviews were undertaken with principal informants: six Muslim leaders, six youth leaders, and six Muslim academics. Expansion description was employed to analyze the data. The results showed that in each community, Muslim leaders played a principal role in supervising youth based on Islamic belief by using different methods depending on the surrounding situations and individual ability. Supervisory budget sources were donation money, Zakat grants, and an endorsement budget from state organizations. However, there were four major problems which caused inefficiency in youth supervision: lack of understanding and definition of the roles and duties of some Muslim leaders, unawareness of the importance of youth supervision, skill and experience deficiencies in youth supervision, and a limited relationship between Muslim leaders and youth groups.